MENINGKATKAN KEMAMPUAN GURU DENGAN BERBANTUAN KEGIATAN WORKSHOP DALAM MENYUSUN PERANGKAT PEMBELAJARAN DI SUNGAI MAJO KECAMATAN KUBU - Sulmi Sulmi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research was motivated by the weakness of teachers in compiling learning devices in the Primary school of Sungai Majo and Teluk Nilap, Kubu Babussalam District, Rokan Hilir Regency. The purpose of this study is to improve the ability of teachers to develop learning tools in Primary schools. The purpose of this study is to improve the ability of teachers to develop learning tools in Primary schools. The action to be taken is to provide a workshop on the formulation of learning devices in Primary schools. The results of the study show, in the assessment of the first cycle syllabus, The average value obtained by the Sungai Majo Elementary School 006 teacher is 67 with sufficient categories. While teachers at Elementary School 002 Teluk Nilap get an average score of 69 in the good category. cycle II, the average syllabus for teachers in Sungai Majo Primary School 006 was 89 with very good categories. While the teachers of Elementary School 002 in the Teluk Nilap amounted to 90 with very good categories. Whereas the assessment in the RPP of the first cycle, teachers in Elementary School 006 Sungai Majo and SDN 002 Teluk Nilap received the same score, which amounted to 67.14 with sufficient categories. After the second cycle, Sungai Majo Primary School 006 got an average score of 90 with a very good category, while the teachers of Elementary School 002 Teluk Nilap scored 91.42 with a very good category. With the results of this study, it can be concluded that with the help of workshops, it can improve the ability of teachers to develop learning tools in the Sungai Majo and Teluk Nilap, Kubu Babussalam District, Rokan Hilir Regency.